The Current and Future States of Diagnostic Tests for Histoplasmosis with a Focus on People with HIV and Disseminated Histoplasmosis - Kenneth Villareal; Austin Price; Alessandro C. Pasqualotto; Nathan C. Bahr (Journal of Fungi, 2023)
Histoplasmosis is caused by Histoplasma capsulatum and, although endemic in large parts of the world, is often underrecognized in many locations. In addition to underrecognition, inadequate availability of diagnostic tests is a major contributor to poor outcomes in disseminated disease in people with HIV. For those with advanced HIV and disseminated disease, antibody testing is less useful. Culture and histopathology can be useful in this situation, but each has limitations, including variable sensitivity by site and, in the case of culture, the need for a biosafety level three laboratory and a long period of growth. Antigen testing has proven useful for disseminated histoplasmosis due to the excellent sensitivity of urine. Yet, turnaround is slower than ideal due to use in a limited number of centers. The development of lateral flow assays has the potential to make for true rapid point-of-care assays for histoplasmosis, but in order to meet that promise, the tests must be widely available and affordable.